2015
DOI: 10.1016/j.rser.2015.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the adoption of photovoltaic systems: The state of the art

Abstract: a b s t r a c tAlthough photovoltaic (PV) systems have become much more competitive, the diffusion of PV systems still remains low in comparison to conventional energy sources. What are the current barriers hindering the diffusion of PV systems? In order to address this, we conducted an extensive and systematic literature review based on the Web of Science database. Our state-of-the-art review shows that, despite the rapid development and maturity of the technology during the past few years, the adoption of PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
127
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(142 citation statements)
references
References 55 publications
8
127
1
6
Order By: Relevance
“…One of the best approaches for theory building is conducting a state of the art review or a systematic literature review [20,[93][94][95]. Therefore, in this paper, written definitions from various scientific publications are gathered and analyzed to gain a good understanding of the SE concept for providing a definition and framework for it.…”
Section: Methodsmentioning
confidence: 99%
“…One of the best approaches for theory building is conducting a state of the art review or a systematic literature review [20,[93][94][95]. Therefore, in this paper, written definitions from various scientific publications are gathered and analyzed to gain a good understanding of the SE concept for providing a definition and framework for it.…”
Section: Methodsmentioning
confidence: 99%
“…There are also key barriers that are general to BIPV adoption, and in some cases, affect the building integration of other renewable energy technologies. Some of these general issues from a more holistic point of view are sociotechnical, management, economic, and policy-related [29] as well as knowledge and information-related [26]. Others include insufficient presentation of BIPV product and project databases, lack of adequate business models, and insufficient dissemination of BIPV information [24].…”
Section: Bipv Façade Applications: Barriers and Strategiesmentioning
confidence: 99%
“…Table 3 gives a detailed overview of the findings of these related studies showing a categorization of the barriers and drivers identified to BIPV application; to clearly identify the issues of concern and potential solutions. • Dedicated government support and incentives [27,[29][30][31][32][33][34] • BIPV implementation policy formation; [28,29,31] • Non-financial incentives as 'green accreditation' and reduction in lending rates [27,28] 5. Gap between PV and building industry [29,30,32] 4. International professional management and collaborations 6.…”
Section: Bipv Façade Applications: Barriers and Strategiesmentioning
confidence: 99%
See 2 more Smart Citations